Analysis of Semarang City Disbudpar Instagram Content Strategy in the New Era of Covid 19: Analisis Strategi Konten Instagram Disbudpar Kota Semarang di Era Baru Covid 19 - Indainanto, Yofiendi; Julianto, Edi Nurwahyu; Pramucitra, Sinta (ETTISAL : Journal of Communication, 2024)
Efforts to grow tourism in the new era of Covid-19 in Semarang City have encouraged the Semarang City Culture and Tourism Office to promote tourism through various media platforms. One strategy is to promote tourism content through social media Instagram @disbudparkotasemarang. Accessibility encourages tourists to search for information on Instagram. This condition encourages content planning not only to display various destinations. This study aims to find out how to analyze the Semarang City Disbudpar Instagram Content Strategy in the New Era of Covid 19?. The method used is qualitative descriptive using The Circular Model of SoMe to analyze the findings. The results show that the @disbudparkotasemarang Instagram account has basically gone through four important stages in planning content, namely: Share, Optimaze, Manage and Engage. The content strategy is carried out by interacting with posts, displaying cultural events, and tours. This strategy is able to attract user attention as seen from the number of likes and comments that are very different. It's just that the implementation hasn't shown good performance, with the engagement rate still at a moderate level of 1.28 percent. Although, there has been an increase, posts, followers and users during 2022. It is important to plan content by paying attention to the level of engagement which is indicated by interactive communication.